Economic and Legal Mechanisms for Harnessing Natural Resource Potential of the Arctic in the Context of Food and Environmental Security - Mitin, Aleksandr Nikolaevich; Voronin, Boris Aleksandrovich; Donnik, Irina Mikhaylovna (Economy of Regions, 2018)
The article presents the methodology for the assessment of the resource potential of the Arctic. The authors analyze the main elements of its economy that are involved in the food supply of both the Arctic regions and the whole country, as well as in export-import transactions. We state facts and figures for the implementation of the Arctic States policies with the field of both potentials in the Northern latitudes and the projects for utilizing living marine resources in previously unexplored waters. We reveal the dependence of the use of Arctic resources from geopolitical, economic and technological changes in the world. Previously, the economic activities in the Artic were conditioned by certain legal regimes. Now it may revised because of the differences in conceptual approaches when determining the external borders and delimitating continental shelf. We characterize the domestic model of Arctic exploration and the food supply system of territories. We identify the current problem of extraction of marine resources, their processing and delivery to the consumer. Пє intersectoral resource economy of the Arctic territories, the difficulties of fishery and fish processing, aquaculture production, the lack of support for local farms cultivating crops and producing of animal genetic resources are inherited from previous economic models. We basic features of the modern economy of the Arctic have significant country-specific differences depending on the policies that are implemented on one or another Arctic territory. Wis is manifested in the conditions created by the state as well as in the level of investment attractiveness and the quality of life. We factors affecting food security in Arctic areas are the following: the access to fishing stocks; support of the agricultural sector and rural households; the formation of state market mechanisms when creating interregional agrofood complexes; respect for animal genetic resources. We recommend enhancing the regulatory, institutional and economic opportunities of coastal regions, creating the conditions for competition development in the extraction and processing of natural resources in the Arctic.